PELEVELAN KINERJA SISWA BERDASARKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII MTS NEGERI JEMBER DALAM MENYELESAIKAN SOAL MATEMATIKA YANG TEKAIT TEMA KOPI - Irawan, Dahlan; Susanto, Susanto; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2015)
Abstract. The research aims to describe level of student’s performance based on the seventh grade student’s critical thinking in solving mathematics question with theme coffe. Data analysis is done based on written test (performance task) and interview techniques. The research subject is all of the sevent grade students at MTs Negeri Jember 1 odd semester in 2016-2017 academic year. The students’ performance level consist of novice, apprentice, practitioner and expert with indicators from the eight standard of critical thingking ability according to Bassham. Most students are in standard of Clarity that only can write everything in the problems or questions given by the researcher , but actually they cannot resolve those problems correctly. Meanwhile, the dominant students are the students who belong to novice level and there is no student who belong to expert level. The reason is the students are not used to do the open questions and they are not used to relate the lessons that they have got. Keywords : The Level of Student's Performance, Critical Thinking, and Performance Task